Double Face 2.0: A lightweight translucent adaptable Trombe wall - Martin Tenpierik; Michela Turrin; Yvonne Wattez; Tudor Cosmatu; Stavroula Tsafou (Spool, 2018)
Double Face 2.0 is a novel solar wall, joining a strong design identity and high technical performances. In response to the need for energy saving, new high-performance building elements are shape-optimised for passive climate design and to increase user engagement. Given a design concept, computational approaches help to optimise and to customise high-performance building elements for any environment. Double Face 2.0 has been developed by research through design involving designing, 3D modelling, robotic FDM printing, prototyping, experimenting, simulating, and simulation-based optimising. An adjustable, lightweight, translucent Trombe wall has been developed, using an insulator (aerogel) and heat storage (phase change material) encapsulated in optimised and customizable shapes. In winter, it captures, stores, and re-radiates heat from the sun (heating); in summer, it captures internal heat (cooling).